The Effect of Using Outline Technique to Improve Students’ Ability in Writing Descriptive (RETAIN, 2018)
AbstrakBahasa inggris mempunyai 4 skill dan mereka dibagi menjadi 2 bagian skill yaitu penerima dan memproduksi skill. Menulis adalah salah satu produksi skill. Ada banyak tekhnik untuk meningkatkan penulisan siswa. Salah satunya ialah outline untuk membantu progres yang sudah digunakan mereka di kelas. Maka dari itu, penelitian ini di teliti untuk menginvestigasi penggunaan outline untuk mengembangkan komponen penulisan seperti konten dan organisasi didalam teks deskriptif. Penelitian tindakan dipilih sebagai desain penelitian. Ini terfokus di penulisan hasil kerja siswa dari segi konten dan organisasi dan kegunaan outline. Satu kelas sebagai partisipasi karena kelas tersebut adalah kelas yang mempunyai permasalahan. Tes pertama dan kedua digunakan untuk pengumpulan data siswa. Setelah menemukan hasil tes pertama, outline langsung diberikan ke siswa. Hasil dari tes pertama dan kedua terdapat perbedaan yang siknifikan dimana tes kedua memilik nilai lebih tinggi dari pada hasil tes pertama. Ini juga ditemukan bahwa outline membantu dalam penulisan siswa terutama dari segi konten dan organisasi hasil tulisan siswa. Maka dari itu, berdasarkan permasalahan di bab pertama bahwa tulisan siswa renda. Ada banyak alasan seperti mereka tidak mengetahui bagaimana mengorganisasi ide-ide mereka, bagaimana menyalin ide mereka ke dalam tulisan. Permasalah-permasalahan sudah terselesaikan menggunakan outline. Itu bisa dilihat dari hasil tulisan deskripsi siswa dan juga bias dilihat dari peningkatan hasil tulian mereka dari segi konten dan organisasi tulisan.Kata kunci: Outline, Menulis, Teks DeskriptifAbstractEnglish has four skills and they are divided into two parts, receptive and productive skills. Writing is one of productive skills in English. There are many techniques to improve writing ability. One of them is outline technique to recall the progress that had been done through the class. Outline is a plan before writing a paper or an essay that can be used for students in the writing class. Therefore, this study is conducted to investigate the use of outline is effective to improve students’ writing component such as content and organization in descriptive text. Action research is chosen as the research design. The focus limited into students writing component especially content and organization and the use of outline. One class was a participant since that class which had a problem. Pre-test and post-test were used to collect the data students’ writing. After the result of pre-test had been scored, outline was given directly. And then, they start to do the post-test. The results found that there is significance changes between pre-test and post-test where post-test has higher score that the pre-test. It is also found that outline helps their writing especially in the content and organization of the students’ essay writing. Therefore, according to the problems in chapter 1 that are students’ writing were low. There are many reasons such as they do not know how to organize their ideas, how to transfer their thought into a writing. Those problems have been solved by using outline. It can be seen from result of their writing descriptive and it can be looked from the improvement of their writing in term of content and organization.Keywords: Outline, Writing, Descriptive text